MODEL IKLIM SEKOLAH DALAM PENINGKATAN MUTU LAYANAN PENDIDIKAN TERHADAP SISWA DI MADRASAH ALIYAH AL-HAKIMIYAH PARINGGONAN - Amiruddin MS; Syafaruddin Syafaruddin; Rosa Hadana Harahap (Jurnal Al-Fatih, 2021)
The school climate, namely the principal of the madrasa, making the academic stages of organizing the curriculum developed in the form of an organization, namely the subject curriculum, field of study curriculum and local content curriculum. management of facilities and infrastructure can be said to be good, where related parties such as teachers are involved at this stage. In addition, the head of the madrasa at this stage conducts a needs analysis aimed at the effectiveness and efficiency of facilities and infrastructure. The supervision carried out by the head of Madrasah Aliyah Al-Hakimiyah Paringgonan has been carried out well, but there are some teachers who do not know the standards of supervision carried out and there are no strict sanctions against teachers who violate the rules.